2015
DOI: 10.1186/s12936-015-0821-1
|View full text |Cite
|
Sign up to set email alerts
|

Submicroscopic carriage of Plasmodium falciparum and Plasmodium vivax in a low endemic area in Ethiopia where no parasitaemia was detected by microscopy or rapid diagnostic test

Abstract: BackgroundMotivated by the success in malaria control that was documented over the last decade Ethiopia is aiming at malaria elimination by 2020 in selected districts. It is currently unknown if asymptomatic, submicroscopic malaria parasite carriage may form a hurdle to achieve elimination. The elimination effort may further be complicated by possible glucose-6 phosphate dehydrogenase (G6PD) deficiency which would hinder the use of 8-aminoquinolines in the elimination efforts.MethodIn February 2014 a community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 38 publications
10
55
2
1
Order By: Relevance
“…Studies in Iran [37] and Sri Lanka [38] reported zero prevalence by the more sensitive methods, indicative of no local transmission and confirmation of malaria elimination. Golassa et al [14] and Tadesse et al [15] reported PCR prevalence ranging from 1.7 to 5.8% in southwest Ethiopia, comparable to the 3.3% prevalence reported in the current study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Studies in Iran [37] and Sri Lanka [38] reported zero prevalence by the more sensitive methods, indicative of no local transmission and confirmation of malaria elimination. Golassa et al [14] and Tadesse et al [15] reported PCR prevalence ranging from 1.7 to 5.8% in southwest Ethiopia, comparable to the 3.3% prevalence reported in the current study.…”
Section: Discussionsupporting
confidence: 88%
“…A relatively high prevalence of subpatent or low parasite density infections, that are often missed by conventional diagnostic methods (microscopy and rapid diagnostic tests) are being reported especially from low transmission settings [7][8][9][10][11][12][13][14]. Such asymptomatic, subpatent infections could be explained by acquired immunity in higher transmission settings [15]. Even in low transmission settings, asymptomatic and subpatent infections might play a role in transmission dynamics, hindering the progress of malaria elimination [14][15][16][17][18][19].…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…In their sample of 1,509 people, 52 (3.4%) were diagnosed as having malaria by microscopic examination, whereas 399 (26%) were positive by PCR. These data, and others like it, consistently demonstrate that microscopically subpatent parasitemia is the rule in Indonesia, as elsewhere (Solomon Islands, the Mekong Region, Horn of Africa, and Amazonia) 16. The long-held presumption that natural immunity to malaria required sustained and intense transmission needs reconsideration.…”
Section: Endemic P Vivax Epidemiologysupporting
confidence: 52%
“…In this province, the regular refresher training courses are organized by both provincial and prefecture level every year to maintain the microscopical test skills from the majority of the counties' level, and there are two mutual-checking microscopists meetings every year, in which the microscopists from all the 13 prefectures bring their positive and negative slides and checked by each other, in addition, the quality control system for the whole provincial microscopical test has been established, provincial reference lab for malaria diagnosis collect the slides quarterly and reviewed the reading accuracy and feedback the result to the administrative department. The number of rapid diagnostic tests (RDTs) that are available and the scale of their use for malaria detection has increased rapidly over the past few years; however, RDTs have a relatively poor detection rate for asymptomatic malaria cases with low parasite densities [10][11][12]. In addition, limited RDT products for malaria have been registered with the State Food and Drug Administration (SFDA) in China; therefore, microscopic examination is still the first choice for malaria diagnosis in most parts of China.…”
Section: Introductionmentioning
confidence: 99%